Analisis Potensi Angin Sebagai Sumber Penggerak Turbin Angin Savonius Di Kabupaten Timor Tengah Selatan (TTS) - Ironis R. Naitio; Arifin Sanusi; Nurhayati Nurhayati (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2021)
Wind energy is an energy that cannot be separated from our daily lives. Wind is one of the renewable energies that will never run out. In addition, wind energy also does not produce pollution that can disturb the environment. This makes wind energy as one of the alternative energy that has great potential, so it is necessary to conduct research for wider utilization and in long -term use. Savonius wind turbine is one of the vertical shaft turbines (VAWT) where the savonius wind turbine has a main rotor that rotates vertically, and can utilize wind from all directions, and can work/rotate at low wind speeds. The method of data analysis that I can use in this research is to take data directly and simultaneously on wind speed, turbine rotation, and others. The results of data analysis obtained: (1) the highest average wind speed for 1 month is 5.62 m/s with a turbine rotation of 845.36 rpm (2) The highest turbine power is 104 W (3) Turbine effective power is 28.08 W (4) and The highest average efficiency is 23.34 % and the lowest is 8.86 %.